Nuclear Chaperone ASF1 is Required for Gametogenesis in Arabidopsis thaliana - Min, Yunsook (Sci Rep, 2019)
Sexual reproduction in flowering plants is distinct from that in animals since gametogenesis requires production of haploid spores, which divide and differentiate into specialised gametophyte structures. Anti-Silencing Function 1 (ASF1) is a histone H3/H4 chaperone involved in chromatin remodeling during cell division, which we have found plays a critical role in gametophyte development in Arabidopsis thaliana. Using mutant alleles for the two ASF1 homologs, asf1a and asf1b, we show that ASF1 is required for successful development of gametophytes and acquisition of fertilisation competency. On the female side, reproductive failure is caused by aberrant development of ovules, leading to gamete degeneration. On the male side, we show both in vitro and in vivo that asf1 mutant pollen tube growth is stunted, limiting fertilisation to ovules nearest the stigma. Consistent with ASF1 importance in gametogenesis, we show that ASF1A and ASF1B are expressed throughout female and male gametogenesis. We show that the gametogenesis defects can be corrected by ASF1A and ASF1B transgenes, and that ASF1A and ASF1B act redundantly. Thus, in contrast to the role of ASF1 in sporophytic cell cycle progression, our data indicate that during reproduction, ASF1 is required for the precise nuclei differentiation necessary for gametophyte maturation and fertilisation.